2019
DOI: 10.1504/ijesb.2019.10004713
|View full text |Cite
|
Sign up to set email alerts
|

The long-term viability of U.S. wine grape vineyards: Assessing vineyard labour costs for future technology development

Abstract: The motivation for this study centres on the labour-and cost-intensive nature of wine grape production and the potential opportunities for robotic technology. The objectives of this study are to develop cost of production budgets for five representative wine grape vineyards in four US states, assess the economic viability of wine grape production under current operating conditions, evaluate labour costs by production task, and identify common production challenges and tasks that could be augmented with robotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Autonomous weeding practices are operations considered to be cost-effective alternatives to conventional practices, as reported by other studies [21,22]. McCorkle et al [24] reported potential positive economic returns for pruning and topping operations in vineyards, which align with the corresponding operations in the present study. Nevertheless, the defoliation and tying operations have generated higher costs in comparison to conventional practices that are carried out manually.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Autonomous weeding practices are operations considered to be cost-effective alternatives to conventional practices, as reported by other studies [21,22]. McCorkle et al [24] reported potential positive economic returns for pruning and topping operations in vineyards, which align with the corresponding operations in the present study. Nevertheless, the defoliation and tying operations have generated higher costs in comparison to conventional practices that are carried out manually.…”
Section: Discussionsupporting
confidence: 86%
“…The literature regarding automation in field crop production via integrating autonomous operations is rather limited [20]. Autonomous robotic operations are mainly focused on weeding operations [21][22][23], while McCorkle et al [24] illustrated the potential economic benefits of autonomous robotic labor in comparison to human labor for selected vineyards in Texas, USA.…”
Section: Introductionmentioning
confidence: 99%
“…The following process of developing a typical Texas vineyard and winery is based on the methods used in McCorkle et al [59,60] and the Strauss [58] method of developing a typical whole-farm model. The first step in this process is collecting farm-level data from representative vineyard owners.…”
Section: Developing the Typical Farm's Budget Modelmentioning
confidence: 99%
“…The consensus reached by only six experts may not fully represent the diversity of the Texas wine industry, particularly in specific regions such as North Texas or the Bell Mountain AVA, as well as wineries outside the Hill Country AVA. However, it is worth noting that a similar sample size has been successfully utilized in previous studies to develop economic models for previously unexplored situations [59]. Furthermore, there is a lack of vineyards currently implementing cluster thinning practices in Texas.…”
Section: Limitations and Future Researchmentioning
confidence: 99%